Negative Social Experiences Mediate the Relationship between Sexual Orientation and Mental Health. Issue 2 (28th January 2022) - Barry, Caitlin; Speed, David; Best, Lisa
ABSTRACT: The lesbian-gay-bisexual (LGB) population experiences a higher rate of psychopathology than the non-LGB population. Minority stress theory (MST) suggests that this pattern of findings is due to the increased negativity that LGB individuals face; however, MST is often employed as a post-hoc explanation for health inequalities as opposed to an a priori approach that explicitly tests this idea and has not been examined in the context of Canadian sexual minorities. Using the 2012 Canadian Community Health Survey—Mental Health (CCHS-MH), we tested the MST on a sample 22, 495 Canadians ( n = 21, 995 non-LGB; n = 500 LGB). Results indicated that respondents' scores on the Negative Social Interactions scale (NSI) partially mediated the relationship between LGB status and both depression and satisfaction with life. The findings suggest that a substantial component of the relationship between sexual orientation and mental health is influenced by deleterious social exchanges.